Uneasy Pursuit: A Screenplay Exploring an Untreated Schizophrenia and Its Impacts on One’s Life - Ivana Faustina; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Mental health has been overlooked in Indonesia for too long. Labels like ‘nuts’ and ‘insane’ are often associated with the matter, creating a stigma that undermines its significance. Therefore, this creative work intends to bring forth the urgency of mental health awareness, especially on women who are more prone to mental illness than men. The chosen topic is schizophrenia, which can result in fatal impacts, including suicide, if left untreated. The story follows Sandra, an Indonesian female police detective who unknowingly is battling schizophrenia while trying to catch a skilled mysterious criminal. After a series of regressions, she grows more miserable, reaches peak devastation when struck by grief, and tries to end her life. However, she manages to overcome the pain and, with the help of proper treatment, puts the illness under control. Conclusively, this work aims to highlight the importance of early treatment and awareness of mental illnesses.